Digital Image Encryption Techniques: Article Review - Jameel, Enas Ali; Fadhel, Sameera Abbas (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In this age of the multi-media, images have an important impact on communication. When users upload images over an insecure communication network, total security is a difficult problem to address in order to maintain image confidentiality. Also, encryption is a technique for keeping images secret. This study gives a basic introduction to cryptography, as well as a concise overview regarding the many image encryption algorithms' elemental security criteria. This paper includes an overview of several image encryption approaches as well as a comparison of discrete image encoding techniques, before coming to a conclusion and recommending future research.